Evaluation of Nursing Students\' Learning Styles Based on VARK Learning Pattern in Ramsar School of Nursing & Midwifery - Zahra Jannat Alipour; Navabi Navvabi; Mehri Jahanshahi (Babol University of Medical Sciences, 2013)
ABSTRACT BACKGROUND AND OBJECTIVE: Learning style is an important factor affecting learning. Knowledge about the nature and types of learning styles in learners can help teachers to adjust their teaching methods with students, learning styles to achieve the desired educational outcomes.This study was conducted to determine nursing students' learning styles based on VARK learning pattern in Ramsar School of Nursing; Midwifery. METHODS: This descriptive cross sectional study was performed with 132 nursing students in Ramsar School of Nursing and Midwifery in 2011-2012. Census was performed and data gathering was conducted by a self report method with a questionnaire. The VARK learning questionnaire (7th version) was used in this study. Finally data were analyzed by SPSS v16 software and descriptive - analytic statistical tests. FINDINGS: The mean age of subjects was 20.73±1.94 years. 93% of nursing students had multiple mode learning style and 7% had single mode learning style. The most common learning style among students with multiple mode learning style was tri-mode (51%). The preferred learning style of students was auditory style with the proportion of 38%. CONCLUSION: According to the prevalence of multiple mode learning style among nursing students and the nature of nursing courses, teachers must use active learning approaches that provide learning for students with multiple mode learning style, so determination of students, dominant learning styles and its conformity with teaching methods and to prepare lesson plans based on learning styles can help educational groups and supervisors to improve and promote learning objectives.